1975
DOI: 10.1242/dev.33.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Experimental cardiac morphogenesis: I. Development of the ventricular septum in the chick

Abstract: An experimental technique utilizing microfiber markers and radioautography was used to study the morphogenesis of the ventricular septum in the chick embryo heart from stages 22 to 33 of Hamburger & Hamilton (1951). Fibers placed in the myocardium of the primitive ventricles of 4-day-old embryos within 250 µm to each side of the future site of the ventricular septum resulted in shortening of the distance between the two fibers until both were found within the myocardium of the septum at 7 days. The fibers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Likewise, the authors suggested that this septum grows passively toward the ventricular cavity as the trabecular pouches develop. However, this coalescence origin was not fully supported by the in vivo selective labeling results in chick embryos 19,21,22,28 . De la Cruz et al 28,85 described that pmIVS appears in the straight-tube heart, precisely at the midline of fusion of the cardiac primordia and at the level of the interventricular grooves (Figure 3B).…”
Section: Ventricular and Atrioventricular Septationmentioning
confidence: 93%
See 1 more Smart Citation
“…Likewise, the authors suggested that this septum grows passively toward the ventricular cavity as the trabecular pouches develop. However, this coalescence origin was not fully supported by the in vivo selective labeling results in chick embryos 19,21,22,28 . De la Cruz et al 28,85 described that pmIVS appears in the straight-tube heart, precisely at the midline of fusion of the cardiac primordia and at the level of the interventricular grooves (Figure 3B).…”
Section: Ventricular and Atrioventricular Septationmentioning
confidence: 93%
“…Although these studies provided valuable information, they did not reflect the true dynamism of the process of cardiogenesis as they were based on histological sections; moreover, the embryos likely presented errors associated with defects in cardiac development. These limitations were initially resolved using in vivo selective labeling experiments with plastic labels carried out in chick embryos [18][19][20][21][22][23][24][25][26][27][28] . This technique allowed longitudinal studies to be carried out since it is possible to temporally trace the structural changes of an embryonic region previously marked with a label.…”
Section: Introductionmentioning
confidence: 99%